Innovative Decarbonization Strategies for Net-Zero Airports: Impacts and Challenges - Zhang Qianxun (MATEC Web of Conferences)
The aviation industry is responsible for approximately 2-3% of global CO2 emissions, with airports contributing significantly through energy consumption, ground operations, and aircraft-related activities. Achieving net-zero emissions requires innovative decarbonization strategies that integrate renewable energy, sustainable aviation fuels (SAFs), electrification, and so on. This paper examines cutting-edge approaches to decarbonizing airports, evaluates their environmental and economic impacts, and discusses their limitation and challenges, including high costs, technological limitations, and regulatory barriers. By analyzing case studies and emerging trends, this paper provides insights into how airports can transition toward sustainability and achieve net zero while maintaining operational efficiency and resilience in a low-carbon future. According to the survey, the most prospective decarbonization strategies include SAFs, RNG, and electrification since these technologies can provide immediate and measurable reductions to CO2 emissions from aircraft, and the costs are relatively low. The paper provides a comprehensive review of the decarbonization methods used by airports currently and points out that the critical needs for improvement are high cost, policy support, and stakeholder collaboration.